Dialyzer Classification and Mortality in Hemodialysis Patients: A 3-Year Nationwide Cohort Study - Abe, Masanori; Masakane, Ikuto; Wada, Atsushi; Nakai, Shigeru; Nitta, Kosaku; Nakamoto, Hidetomo (Frontiers in Medicine, 2021)
Background: Dialyzers are classified as low-, high-, and super high-flux membrane dialyzers internationally and as types I, II, III, IV, and V based on β2-microglobulin clearance rate in Japan. Type I dialyzers correspond to low-flux membrane dialyzers, types II and III to high-flux, and types IV and V to super high-flux. Here we aimed to clarify the association of dialyzer type with mortality. Methods: This nationwide prospective cohort study analyzed data from the Japanese Society for Dialysis Therapy on 2010 and 2013. We enrolled 238,321 patients on hemodialysis who were divided into low, high, and super high-flux groups in the international classification cohort and into type I to V groups in the Japanese classification cohort. We assessed associations of each group with 3-year all-cause mortality using Cox proportional hazards models and performed propensity score matching analysis. Results: By the end of 2013, 55,308 prevalent dialysis patients (23.2%) had died. In the international classification cohort, the hazard ratio (95% confidence interval) was significantly higher in the low-flux group (1.12 [1.03-1.22], P = 0.009) and significantly lower in the super high-flux group (0.95 [0.92-0.98], P = 0.006) compared with the high-flux group after adjustment for all confounders. In the Japanese classification cohort, the hazard ratios were significantly higher for types I (1.10 [1.02-1.19], P = 0.015) and II (1.10 [1.02-1.39], P = 0.014) but significantly lower for type V (0.91 [0.88-0.94], P < 0.0001) compared with type IV after adjustment for all confounders. These significant findings persisted after propensity score matching in both cohorts. Conclusions: Hemodialysis using super high-flux dialyzers might reduce mortality rates. Furthermore, type V dialyzers are superior to type IV dialyzers in hemodialysis patients.